Levosimendan Ameliorates Post-resuscitation Acute Intestinal Microcirculation Dysfunction Partly Independent of its Effects on Systemic Circulation: A Pilot Study on Cardiac Arrest in a Rat Model. Issue 4 (October 2021) - Jia, Tianyuan; Wang, Shiwei; Luo, Chengzhun; Wang, Zida; Liu, Guoxiang; Shang, Zhaoming; Lu, Xiaoye; Yang, Qian; Zhu, Changqing
ABSTRACT: Background: Cardiac arrest (CA) is recognized as a life-threatening disease; however, the initial resuscitation success rate has increased due to advances in clinical treatment. Levosimendan has shown potential benefits in CA patients. However, its exact function on intestinal and systemic circulation in CA or post-cardiac arrest syndrome (PCAS) remained unclear. This study preliminarily investigated the link between dynamic changes in intestine and systemic hemodynamics post-resuscitation after levosimendan administration. Methods: Twenty-five rats were randomized into three groups: sham control group (n = 5), levosimendan group (n = 10), and vehicle group (n = 10). Intestinal microcirculation was observed using a sidestream dark-field imaging device at baseline and each hour of the return of spontaneous circulation (⩽6 h). Systemic hemodynamics, serum indicators of cardiac injury, and tissue perfusion/metabolism were measured by echo-cardiography, a biological signal acquisition system, and an enzyme-linked immunosorbent assay, respectively. Results: Myocardial injury and global and intestinal perfusion/metabolism were significantly improved by levosimendan treatment. There was no statistically significant difference in the mean arterial pressure values between the vehicle and levosimendan groups ( P  > 0.05). The intestinal and systemic circulation measurements showed poor correlation (Pearson r-value of variable combinations in the levosimendan group was much less than 0.75; P  < 0.01, levosimendan vs. vehicle group). Conclusions: Levosimendan significantly reduced the cardiac injury and corrected the metabolic status in an experimental rat model of ventricular fibrillation induced CA and cardiopulmonary resuscitation. Levosimendan may ameliorate PCAS-induced intestinal microcirculation dysfunction, partly independent of its effects on macrocirculation. Abstract : Supplemental Digital Content is available in the text